CORRELATION OF ONSHORE-OFFSHORE TERTIARY BASIN OF SOUTHWESTERN PENINSULAR MALAYSIA - CHUNG, WEI KIAT (Universiti Teknologi PETRONAS, 2014)
This project is focused on 3 Malaysian tertiary basins: The onshore Batu Arang Basin and the offshore Port Klang and Sabak Graben. This project aims to determine the basin formation history and the mechanism driving the rifting. The methodology consists of deep marine seismic interpretation, seismic facies analysis, structural analysis, geomorphology and regional tectonics fieldwork in achieving the project’s objective. The research on the regional tectonics will be aided by the study on Shuttle Radar Tomography Mission (SRTM) data rendered in Global Mapper 15. Structural analysis of Port Klang Graben is conducted to map out the basement faults in relation to rifting during the Eocene and the syn-depositional sedimentary structures in the basin. Keywords: Seismic facies analysis; Depositional environments; Regional Tectonics